2018
DOI: 10.1038/s41537-018-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

NEURAPRO: a multi-centre RCT of omega-3 polyunsaturated fatty acids versus placebo in young people at ultra-high risk of psychotic disorders—medium-term follow-up and clinical course

Abstract: This study reports a medium-term follow-up of a randomised, double-blind, placebo-controlled trial of omega-3 polyunsaturated fatty acids (PUFA) in ultra-high risk for psychosis (UHR) patients. Primary outcomes of interest were transition to psychosis and symptomatic and functional outcome. A secondary aim was to investigate clinical predictors of medium-term outcome. Three hundred four UHR participants were recruited across 10 specialised early psychosis services in Australia, Asia, and Europe. The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Omega-3 fatty acids show anti-inflammatory activity (Chen et al, 2015). As noted in the section on The at-risk mental state above, initial findings of a decreased risk of progression to psychosis in an ultra-high risk cohort with omega-3 (Amminger et al, 2010(Amminger et al, , 2015 were not replicated (McGorry et al, 2017;Nelson et al, 2018). A recent meta-analysis of 20 RCTs reported no improvement in positive or negative symptoms in schizophrenia (Cho et al, 2019b).…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 97%
“…Omega-3 fatty acids show anti-inflammatory activity (Chen et al, 2015). As noted in the section on The at-risk mental state above, initial findings of a decreased risk of progression to psychosis in an ultra-high risk cohort with omega-3 (Amminger et al, 2010(Amminger et al, , 2015 were not replicated (McGorry et al, 2017;Nelson et al, 2018). A recent meta-analysis of 20 RCTs reported no improvement in positive or negative symptoms in schizophrenia (Cho et al, 2019b).…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 97%
“…Negative symptoms and cognitive deficits frequently persist and contribute substantially to impaired functional outcome. Loewy et al (73) Cognitive functioning The variability in outcomes for CHR-P patients requires treatments that offer the prospect of high benefit and low risk McGlashan et al 20Prevention psychosis The chronicity of schizophrenia determines the primary rationale for studies of early intervention for this disorder McGorry et al (19) Prevention psychosis Progression to psychosis is neither inevitable nor predetermined and it may be possible to delay the onset of psychosis McGorry et al (28,29) Prevention psychosis Treatment strategies should relieve distress, improve functioning, and reduce the risk for progression to a psychotic illness Miklowitz et al 74Reduction of attenuated positive psychotic symptoms…”
Section: Oxytocinmentioning
confidence: 99%
“…Over the following years, the trough of disillusionment for effective preventive treatments for psychosis onset received additional corroborating support. Two large randomized controlled trials showed that neither cognitive behavioral therapy [2012 (27)] nor Omega-3 interventions [2017/2018 (28,29)] are effective in reducing the progression to psychosis from a CHR-P state. Overall, seven new trials involving 992 new CHR-P participants (an increase of more than 50%) have been published since the last meta-analysis that informed the NICE guidelines (30).…”
mentioning
confidence: 99%
“…This is despite a number of meta-analyses clearly showing that it is possible to delay transition by 24-48 months at least, with a 50% risk reduction [16,17,19,37]. In recent trials, transition rates in both active and control groups are comparatively low (8-11%), which may be partly due to the efficacy of the "background" psychosocial intervention provided in all treatment arms [38], and symptomatic and functional outcomes are variable but favourable at longer term follow up and better than at baseline [39]. These results are produced through largely transdiagnostic and variable psychosocial interventions.…”
Section: Interventionmentioning
confidence: 99%